Dendritic cells: key players in human herpesvirus 8 infection and pathogenesis - Campbell, Diana M.; Rappocciolo, Giovanna; Jenkins, Frank J.; Rinaldo, Charles R. (Frontiers in Microbiology, 2014)
Human herpesvirus 8 (HHV-8; Kaposi’s sarcoma-associated herpesvirus) is an oncogenic gammaherpesvirus that primarily infects cells of the immune and vascular systems. HHV-8 interacts with and targets professional antigen presenting cells and influences their function. Infection alters the maturation, antigen presentation, and immune activation capabilities of certain dendritic cells (DC) despite non-robust lytic replication in these cells. DC sustain a low level of antiviral functionality during HHV-8 infection in vitro. This may explain the ability of healthy individuals to effectively control this virus without disease. Following an immune compromising event, such as organ transplantation or human immunodeficiency virus type 1 infection, a reduced cellular antiviral response against HHV-8 compounded with skewed DC cytokine production and antigen presentation likely contributes to the development of HHV-8 associated diseases, i.e., Kaposi’s sarcoma and certain B cell lymphomas. In this review we focus on the role of DC in the establishment of HHV-8 primary and latent infection, the functional state of DC during HHV-8 infection, and the current understanding of the factors influencing virus-DC interactions in the context of HHV-8-associated disease.